A relação entre fragmentos estruturais oriundos de produtos naturais e compostos bioativos - Nascimento-Júnior, Nailton M. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2015)
This review aims to highlight some structural fragments derived from natural products, which are present in several bioactive compounds, most of them used as drugs. In this context, are described the amino acids, purines and pyrimidines, steroids, carbohydrates, as well as other structural subunities present in the bioactive compounds that will be shown in this manuscript, complemented with their therapeutic targets or treated symptoms.
The relationship between structural fragments derived from natural products and bioactive compounds
Keywords: Bioactive compounds; Medicinal chemistry; Natural products; Structural fragments